ESG em empresas com estrutura de controle por fundos de pensão: um estudo sobre reputação, risco e desempenho - Oliveira, Genize Santos de (2024)
When investigating the impact of environmental, social, and governance (ESG) practices on Brazilian companies with pension fund control structures, this study faces the challenge of clarifying the relationship between ESG variables and indicators of change, risk, and performance in these organizations. The research population comprises 918 companies, with a sample of 105 companies, over the period from 2010 to 2022. Therefore, the general objective of this study is to examine the effects of ESG practices on these three critical aspects of companies that have pension fund control structures. To achieve this purpose, we designed a quantitative approach, with data collection conducted from the Economática® and Refinitiv Eikon® databases, accessible through the B3 website. These databases encompass publicly traded companies associated with pension funds. The data analysis is conducted using the Generalized Method of Moments (GMM-Sys), a statistical and economic technique that aims to estimate relationships in models by minimizing the discrepancy between observed data points and theoretical points. This methodological choice reflects the intention to thoroughly investigate the complex interactions between the variables. Additionally, the reputation variable was analyzed using the Logit Model. This study is of great relevance for several reasons. Firstly, it addresses a significant research gap by focusing on the intersection between ESG practices and companies with pension fund control structures in the Brazilian context. Furthermore, the choice to use GMM-Sys demonstrates a commitment to the accuracy of estimates and the consideration of possible correlations between variables during panel analyses. The results showed that the variable representing the relationship between ESG and pension funds is statistically significant and is associated with ROE and ROA, indicating that ESG practices serve as a moderator for the negative effects of pension fund control structures on company performance, reducing market risk. In summary, the research provided important insights into the influence of pension funds on Brazilian companies, highlighting both the positive aspects and the challenges associated with integrating ESG practices and pension fund management.